PENGARUH VARIASI LAMA FERMENTASI TERHADAP KANDUNGAN PROTEIN PADA TAPE TALAS (Colocasia esculenta) SEBAGAI SUMBER BELAJAR BIOLOGI SMA KELAS XII PADA MATERI BIOTEKNOLOGI PENGOLAHAN BAHAN PANGAN - Eka Baskara Prasetyajati Agus Sujarwanta (Bioedukasi Jurnal Pendidikan Biologi, 2015)
Abstract: The purpose of this study was 1 ) to determine whether or not the effect of fermentation time variation of the protein produced on tape taro. 2 ) to determine variations in fermentation hours to obtain the highest protein content of the tape taro. The study design used was completely randomized design with 4 treatments and 5 replications. Parameters measured were crude protein content and organoleptic tape taro. The results showed that the fermentation time affect the protein content of the resulting tape taro, the highest protein content in treatment C (fermented 60 hours ) resulted in as much as 3.888 % protein. Based on the test results BNJ all treatments were significantly different with the exception of treatment B and D. Benefits in the manufacture of tape taro research are: the lecturer can be used as teaching materials practicum taro tape processing methods on the biology subject matter in the form of LKPS biotechnology, and science can contribute to the reader about alternative ways of processing of taro as a traditional food.